The Shortest Path to the Health Services in Baghdad Using the Improved Dijkstra Algorithm on mobile device - Dena Kadhim Muhsen; Rihab Flaih Hassan (Journal of Madenat Alelem University College, 2019)
Shortest path problem is very significant in the study of transportation and communication network. Travelling is important part of daily life. Therefore the optimal shortest path (SP) to the particular destination becomes inevitable to reduce costs, losses in productivity, pollutions, and risks etc. An appropriate algorithm is used to find the shortest path between two known vertices is Dijkstra’s algorithm which is submitted by the famous Dutch computer scientist Edsger W. Dijkstra, which was recognized as the optimal algorithm that can be applied to obtain the shortest path from a vertex (node) to any other vertex. In this paper design an android application based on improved Dijkstra algorithm which used constraint function and develop this algorithm by using priority queue and determine the source by GPS .This Application assist to find the shortest path to hospital from user location, time, distance, all hospital information related (like hospital name, contact number, e-mail, and specialization). It is helpful in terms of reducing transition time, effort, and cost. Android mobile’s application considered as a guide for users toward the hospitals in Karada region from many locations within Baghdad city.